1990
DOI: 10.1037/0735-7044.104.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Associative learning and memory for an antinociceptive response in the spinalized rat.

Abstract: Prior research suggests that associative and memorial processes can modulate the activation of the endogenous antinociceptive systems. It has been generally assumed that forebrain systems play an essential role in mediating the impact of these processes. The present experiments explored whether the behavioral effects indicative of associative and memorial processes can be obtained in spinalized rats. Experiment 1 demonstrated that a conditioned nonopioid antinociception can be established after rats have exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…We found that subjects exhibited longer latencies during the CS+, a form of conditioned antinociception (Fig. 2B; Grau, Salinas, Illich, & Meagher, 1990). Further work showed that this mechanism exhibited a number of Pavlovian phenomena, including latent inhibition, blocking, and overshadowing (Illich, Salinas, & Grau, 1994).…”
Section: Pavlovian Conditioningmentioning
confidence: 69%
“…We found that subjects exhibited longer latencies during the CS+, a form of conditioned antinociception (Fig. 2B; Grau, Salinas, Illich, & Meagher, 1990). Further work showed that this mechanism exhibited a number of Pavlovian phenomena, including latent inhibition, blocking, and overshadowing (Illich, Salinas, & Grau, 1994).…”
Section: Pavlovian Conditioningmentioning
confidence: 69%
“…Consistent with this idea, some types of conditioned autonomic and behavioral responses, including analgesia, can be acquired in decerebrate animals and humans (Berntson & Micco, 1976; Berntson, Tuber, Ronca, & Bachman, 1983) or in the isolated spinal cord (Grau, Salinas, Illich, & Meagher, 1990), suggesting that they rely on associative learning in subcortical systems. In addition, conditioned responses are often mediated by synaptic plasticity in specific pathways (Antonov, Antonova, Kandel, & Hawkins, 2001; Glanzman, 1995; Hawkins, Abrams, Carew, & Kandel, 1983; Johansen, Cain, Ostroff, & LeDoux, 2011).…”
Section: Introductionmentioning
confidence: 78%
“…To deal with partial loss of brain inputs and to produce locomotor behavior after an iSCI, the spinal cord could have learned and "memorized" a new mode of functioning . Such spinal mechanisms have been described previously after SCI (Grau et al, 1990(Grau et al, , 1998Martinez et al, 2012) or nerve lesions (Bouyer and Rossignol, 2003a,b;Rossignol, 2008, 2009) and highlight the role of past experiences in shaping the function of the spinal cord (Loeb, 1993). Such spontaneous spinal remodeling must be taken into account when interpreting the locomotor pattern observed in our trained cats after spinalization.…”
Section: Discussionmentioning
confidence: 98%